Policy Adaptation as Impact of Coronavirus Diseases 2019 in Indonesia: Economic and Social Perspectives in 2020 - Bambang Irawan (Institut Ilmu Sosial dan Manajemen STIAMI, 2022)
There are two purposes of this paper. First, to describe the selected strategy as an impact of coronavirus diseases 2019 (COVID-19) in Indonesia. Second, how is the government's response through policies in the economic sector and social life as well as look at the challenges in reducing risks in future. This paper used a viewpoint design for countermeasures of COVID-19 in Indonesia. The policy adaptation made by the government is aimed at economic and social strategies. Build Back Better policy will be the principle in adapting policies in the economic and social fields for Indonesia. There are three strategy for Build Back Better-based policies in the response to Covid-19 in Indonesia. They are building back stronger, building banck faster and building back more inclusiveness. This paper explain information about impact of COVID-19 in Indonesia, how is the government's strategy and policy adaptation carried out in dealing with it, and policy challenges in the economic and social fields in future.